Anaplastic lymphoma kinase-positive anaplastic large cell lymphoma diagnosed in a 90-year-old Japanese woman with simultaneous rearrangements of T-cell receptor and immunoglobulin genes: A case report - Kenji Yorita; Miki Mizobuchi; Munenori Uemura; Hironori Haga; Takashi Takeda; Katsushi Miyazaki; Kazuhiko Tahara; Satoshi Ito; Kimiko Nakatani (Elsevier, 2023)
Anaplastic lymphoma kinase-positive (ALK+) anaplastic large cell lymphoma (ALCL) is a T-cell lymphoma consisting of large lymphoid cells expressing ALK and CD30. It frequently occurs in patients younger than 30 years. However, this case reports a 90-year-old Japanese woman with ALK+ ALCL. The clinicopathological and genetic results of our case are presented. Although the clinical diagnosis suggested lymphoma with enlarged left supraclavicular and axillary lymph nodes and high levels of soluble interleukin 2 receptors, the initial pathological diagnosis suggested metastasis of undifferentiated carcinoma. This is attributed to the cohesive growth with fibrous stroma and immunohistochemical findings, which were positive for epithelial membrane antigen and negative for leukocyte common antigen. Additional immunohistochemistry revealed positivity for ALK and CD30, and Southern blot analysis demonstrated the rearrangement of T-cell receptor and immunoglobulin genes. Pathologists should include ALCL as a differential diagnosis when epithelial membrane antigen-positive large tumor cells lack pancytokeratins and leukocyte common antigen. Moreover, the occurrence of ALK+ ALCL should not be overlooked in older patients.